PTU-247 Does enhanced recovery after colorectal surgery increase the incidence of parastomal hernias?. (22nd June 2015) - Houghton, NR; Lauder, J; Alldis, J; Craig, C
Abstract : Introduction: Evidence supporting the benefits of enhanced recovery after surgery (ERAS) protocols is abundant; however there is no published data on how ERAS may affect the incidence of parastomal hernias. Method: Retrospective, observational, single centre cohort study of patients who underwent elective or emergency operations with stoma formation from January 2006 until March 2013. The cohort was split into ERAS and traditional recovery, and a review of case-notes and stoma nurse records allowed identification of those who developed parastomal hernias at any time point post-operatively. Results: 208 patients were included; 95 underwent a traditional recovery, and 113 underwent ERAS. The demographics of these 2 groups were comparable. 14.74% non-ERAS patients (n = 14) developed parastomal hernias compared to 34.51% (n = 39) in the Enhanced Recovery group (p = 0.0011). Conclusion: This study demonstrated a significantly increased incidence of parastomal hernias in those undergoing enhanced recovery, consistent with the earlier postoperative mobilisation. While the other benefits of ERAS outweigh this risk, this reality of modern post-operative care should reinvigorate the use of scrupulous surgical technique, and consideration of stoma site reinforcement options. Disclosure of interest: None Declared. References: Gravante G, Elmussareh M. Enhanced recovery for colorectal surgery: practical hints, results and future challenges. World J Gastrointest Surg. 2012;4(8):190–8 Chestovich PJ, Lin AY, Yoo J. Fast-track pathways in colorectal surgery. Surg Clin North Am. 2013;93(1):21–32 Lv L, Shao YF, Zhou YB. The enhanced recovery after surgery (ERAS) pathway for patients undergoing colorectal surgery: an update of meta-analysis of randomized controlled trials. Int J Colorectal Dis. 2012;27(12):1549–54 Abraham N, Albayati S. Enhanced recovery after surgery programs hastens recovery after colorectal resections. World J Gastrointest Surg. 2011;3(1):1–6 Godbout JP. Glaser R. Review Stress-induced immune dysregulation: implications for wound healing, infectious disease and cancer. J Neuroimmune Pharmacol. 2006;1(4):421–7 Boyapati L, Wang H. Review the role of stress in periodontal disease and wound healing. Periodontol 2000. 2007;44:195–210 Hotouras A, Murphy J, Thaha M, Chan CL. The persistent challenge of parastomal herniation: a review of the literature and future developments. Colorectal Dis 2013;15(5):e202–14 Sohn YJ, Moon SM, Shin US, Jee SH. Incidence and risk factors of parastomal hernia. J Korean Soc Coloproctol 2012;28(5):241–6